ANALISIS EFEKTIVITAS PROBLEM BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DI SEKOLAH - Erlin Melinah; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Critical thinking skills are one of the most important competencies to be developed among students at school in order to face various challenges in the learning process. However, in practice, the learning process is still more focused on the teacher so that it does not provide many opportunities for students to hone these skills. One alternative learning method that can be applied is Problem Based Learning (PBL), which prioritizes problem solving as a context in learning. This study aims to assess the effectiveness of the application of PBL in improving students' critical thinking skills in schools. The method used is a Literature Study by reviewing 13 national journal articles indexed by SINTA that were published in the 2021-2026 range as well as 2 relevant reference books. The results of the study show that the effective implementation of PBL can improve students' critical thinking skills, especially in analysis, evaluation, and problem solving, as well as increase student participation and involvement in the learning process. In addition, PBL activities are also influenced by several factors, including teacher readiness, learning planning, media utilization, and student character. Thus, PBL is an effective learning model in developing critical thinking skills of elementary school students if implemented optimally.